(untitled) (International journal of artificial intelligence, 2025)
This study examines tourists' perceptions of sustainable development in Uzbekistan's two main tourist centers – Samarkand and Bukhara. Using mixed methods, including a survey of 210 tourists, 15 stakeholder interviews, and field observations, an analysis was conducted to assess visitors' perceptions of the environmental, sociocultural, and economic aspects of sustainability. The results show that tourists highly value architectural heritage, cultural authenticity, and community-based initiatives, but express concerns about commercialization, waste disposal issues, and a lack of "green" infrastructure. Samarkand is perceived as a city that is rapidly modernizing and offering improved conditions for tourists, but risks losing its authenticity. Bukhara, on the other hand, is considered more authentic but faces limited infrastructure and inadequate management of tourist flows. The results show that visible sustainable practices – such as green infrastructure, support for local crafts, and community participation – increase tourist satisfaction and loyalty. In conclusion, the need for closer cooperation between government bodies, the private sector, and local residents to integrate sustainability principles into the development of cultural tourism is emphasized. Strengthening green infrastructure, digital tourism flow management, and the involvement of local communities will help balance tourism growth with the preservation of cultural heritage. The results can help Central Asia create policies and practices for sustainable tourism, which will make Uzbekistan a more responsible and competitive cultural tourism destination.